The Generalized Riemann Problem for a Scalar Combustion Model-the Perturbation on Initial Binding Energy (Journal of Partial Differential Equations, 2020)
In this paper, we study the generalized Riemann problem for a scalar Chapman-Jouguet combustion model in a neighborhood of the origin on upper half of the (x, t) plane. We focus our attention on the perturbation on initial binding energy. Under the entropy conditions, the solutions are obtained constructively. It shows that the perturbed Riemann solutions possess the structural stability except the case that the corresponding Riemann solutions contain CJDT, for which CJDT may transform into SDT after perturbation on initial binding energy in the neighborhood of the origin.